ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN KUALITAS LAPORAN KEUANGAN PADA BADAN KEUANGAN DAN ASET DAERAH (BKAD) KABUPATEN SIDENRENG RAPPANG - Eva Rahmawati; Salida, Amrizal; Taufiq, Muhammad (Paser Institute Of Accounting and Finance, 2024)
This study aims to analyze the Accounting Information System in Improving the Quality of Financial Reports at the Office of the Financial and Regional Asset Agency of Sidenreng Rappang Regency. Data Collection Was Carried Out Using the Mix Method Method using the type of systematic literature riview designs and using a sample of 57 respondents using the purposive sampling technique as a method of data collection. Data analysis used is descriptive percentage analysis of data processing techniques carried out using Statistical Product and Service Solution (SPSS).The conclusion in this study is that the financial report at the Office of the Financial and Regional Asset Agency of Sidenreng Rappang Regency is able to produce quality financial reports based on the elements of Relevance, Reliable, Comparability and Understandability. And the Utilization of the Accounting Information System of the Office of the Financial and Regional Asset Agency of Sidenreng Rappang Regency is able to produce quality financial reports based on aspects of output design, file and database design, input design, program design, procedure design and supervision design.